The Significance of TGF-β Expression in Predicting Lymphovascular Invasion and Lymph Node Metastasis in Colorectal Cancer - Aini, Julpa Nurul; Aswiyanti Asri; Noza Hilbertina; Tofrizal; Avit Suchitra; Husna Yetti (HM Publisher, 2025)
Background: Colorectal cancer (CRC) is a major health burden globally. The prognosis of CRC is strongly influenced by the presence of lymphovascular invasion (LVI) and lymph node (LN) metastasis. Transforming growth factor-beta (TGF-β) is a cytokine with a complex role in CRC progression. This study aimed to evaluate the significance of TGF-β expression in predicting LVI and LN metastasis in CRC. Methods: This cross-sectional study involved 50 patients diagnosed with CRC. The expression of TGF-β was assessed using immunohistochemical staining and the Allred scoring system. The relationship between TGF-β expression and the presence of LVI and LN metastasis was analyzed using the Chi-square test. Results: High TGF-β expression was significantly associated with both LVI (p = 0.011) and LN metastasis (p = 0.012) in CRC. Patients with high TGF-β expression had a higher risk of LVI and LN metastasis compared to those with low TGF-β expression. Conclusion: TGF-β expression is a significant predictor of LVI and LN metastasis in CRC. This finding has potential implications for risk stratification and treatment decisions in CRC patients.